2020
DOI: 10.1002/pc.25838
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polyurethane composites reinforced with halloysite and carbon nanotubes

Abstract: Polyurethane composites were synthesized using carbon nanotube (CNT) and CNT‐halloysite (HNT) hybrid in different amounts. Thermal, rheological, and mechanical properties of the composites were studied using thermogravimetric analysis, rheometrics mechanical spectrometry, dynamic mechanical thermal analysis, stress‐strain analysis, and hardness measurement. In this context, phase separation, elastic modulus, the Young's modulus, damping, tensile strength, ductility, thermal degradation, hardness, and conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…With a further increase in the nanofiller content, the intensity of the hydrogen-bonded N-H stretching was slightly decreased due to a decrease in phase separation. [27,28] In the research conducted by Pourmohammadi-Mahunaki et al, [29] the DPS was measured by a similar approach, and it was observed that with the increase in the CNT content from 0.1 to 0.8, the DPS values slightly increased.…”
Section: Chemical Characterizationmentioning
confidence: 97%
“…With a further increase in the nanofiller content, the intensity of the hydrogen-bonded N-H stretching was slightly decreased due to a decrease in phase separation. [27,28] In the research conducted by Pourmohammadi-Mahunaki et al, [29] the DPS was measured by a similar approach, and it was observed that with the increase in the CNT content from 0.1 to 0.8, the DPS values slightly increased.…”
Section: Chemical Characterizationmentioning
confidence: 97%
“…Many researchers have reported the improvement of thermo-mechanical and chemical properties of polymer HNT samples. [23][24][25][26][27][28][29][30][31][32] HNT can raise the fracture stiffness of epoxy system minus reducing the modulus, strength and thermal constancy. [33] Moreover, HNT enhance the crystallization temperature, glass transition temperature and crystallinity of polyamide-11 (PA11) nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have stated that the mixture of HNTs with polymer media enhances the thermal and mechanical properties [41][42][43][44]. Prashantha et al [45] mixed neat HNT and quaternary ammonium salt-treated HNTs with polypropylene.…”
Section: Introductionmentioning
confidence: 99%